Development of the GIMALONG Interactive Video to Promote Prosocial Behavior and Digital Literacy in Early Childhood - Haniya Haniya; Yes Matheos Lasarus Malaikosa; Wulan Patria Saroinsong; Andi Kristanto; Ruqoyyah Fitri; Utari Dewi (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Prosocial behavior and digital literacy are critical domains in early childhood development but remain under-stimulated due to limited instructional media. This study evaluates the feasibility and effectiveness of the GIMALONG interactive video, designed to foster sharing, collaboration, and helping behaviors while enhancing digital literacy in children aged 5ÔÇô6 years. Using a Research and Development (R&D) approach with the ADDIE model, the product underwent expert validation and was tested through individual (2 children), small group (8 children), and large group (25 children) trials. Data were collected via observation, questionnaires, and pretest-posttest instruments, then analyzed using the N-Gain formula. The results showed high effectiveness, with N-Gain scores for prosocial behavior and digital literacy consistently in the high category across all phasesÔÇöindividual (0.8617; 0.8574), small group (0.8853; 0.8376), and large group (0.8394; 0.8142). These findings support the use of GIMALONG as a feasible and impactful tool to support character and digital competency development in early learning environments.┬á┬á